(untitled) (Journal of Scientific Research, 2024)
Three-phase induction motors are extremely popular and almost ubiquitous in industrial applications. Issues related to starting and speed control of these motors are of great importance in performance determination. This paper presents the speed control of a 3-phase induction motor using a Support Vector Machine (SVM) based classifier. A thyristorised voltage controller regulates the motor speed by utilizing the speed-voltage proportionality. Input to the controller is a multiclass SVM classifier that has been trained to estimate the appropriate firing angle ’‘α’’ for the desired torque-speed combination. A soft starter is also included in the model and, as demonstrated, gives a proper time variation to ’‘α’’. The simulation findings show that the soft starter’s progressive increase in the motor supply voltage significantly reduces the amplitude and the pulsating nature of the starting current and Torque of the motor. The performance of the SVM controller and the soft starter at various torque speed combinations are evaluated on the model and found to be satisfactory.